Designing Electronic Systems Using SystemC and SystemC–AMS - V. A. Alekhin (Российский технологический журнал)
Current trends in the design of electronic systems is the use of embedded systems based on systems on a chip (System-on-Chip (SoC)) or (VLSI SoC). The paper discusses the design features of electronic systems on a chip using the SystemC design and verification language. For the joint design and simulation of digital systems hardware and software, seven modeling levels are presented and discussed: executable specification, disabled functional model, temporary functional model, transaction-level model, behavioral hardware model, accurate hardware model, register transfer model. The SystemC design methodology with functional verification is presented, which reduces development time.The architecture of the SystemC language and its main components are shown. The expansion of SystemC–AMS for analog and mixed analog-digital signals and its use cases in the design of electronic systems are considered. Computing models are discussed: temporary data stream (TDF), linear signal stream (LSF) and electric linear networks (ELN). The architecture of the SystemC–AMS language standard is shown and examples of its application are given. It is shown that the design languages SystemC and SystemC–AMS are widely used by leading developers of computer-aided design systems for electronic devices.